Individual and community level maternal factors for zero-dose children in Ethiopia using mini-EDHS 2019: a mixed effects model - Anteneh Kassa Yalew; Werkneh Melkie Tilahun; Meron Asmamaw Alemayehu; Tigabu Kidie Tesfie; Muluken Chanie Agimas; Mekuriaw Nibret Aweke; Worku Necho Asferie; Moges Tadesse Abebe (BMJ Open)
Introduction Zero-dose children refer to a child who has not yet received any childhood vaccines. Globally, zero-dose children are the major public health problem. In sub-Saharan African countries, one among five children do not have access to vaccines. But the efforts to identify the factors contributing to the zero-dose children are not well addressed in Ethiopia.Objectives To assess individual and community-level maternal factors of zero-dose children in Ethiopia using mini-Ethiopian Demographic Health Survey 2019.Methods A secondary analysis of a cross-sectional study was used among a total of 3208 participants. STATA-14 was used for descriptive and multilevel binary logistic regression (mixed effects model) analysis. Model selection was conducted using Akaike information criteria. To identify significant factors for zero-dose children, a p value of <0.05 with 95% CI was used.Results The prevalence of zero-dose children among children aged 12–35 months was 523 (16.3%, 95% CI 15% to 17.6%). Women with no antenatal care follow-up (adjusted OR (AOR)=1.55, 95% CI 1.02 to 2.35), uneducated women (AOR=1.47, 95% CI 1.11 to 1.95), women who gave birth at home (AOR=1.39, 95% CI 1.04 to 1.86), women who had poor wealth index (AOR=2.15, 95% CI 1.62 to 2.85) and women from low proportions of community media exposure (AOR=1.39, 95% CI 1.13 to 1.71) were the risk factors for zero-dose children in Ethiopia.Conclusion Compared with previous studies, the prevalence of zero-dose children was low in Ethiopia. Variables like urban residence, no education, home delivery, poor wealth index, no antenatal care(ANC) visit and women from low proportions of community media exposure were the risk factors for zero-dose children in Ethiopia. Therefore, expanding maternal health services and media access for women is highly recommended to reduce zero-dose children mortality.